Systems, Software and Services Process Improvement : 27th European Conference, EuroSPI 2020, Düsseldorf, Germany, September 9-11, 2020, Proceedings /: 27th European Conference, EuroSPI 2020, Düsseldorf, Germany, September 9-11, 2020, Proceedings. (2020) - Unknown
No abstract available